Unveiling the deformation and crack mechanism of glass nanostructure embossing: A molecular dynamics study at experimental scale - Xueguang Cui; Ping He; Yingjie Xu; Hao Huang; Wuyi Ming; Weiwei Zhang (PLoS ONE, 2026)
Glass nanostructure embossing is a critical manufacturing process for producing high-precision glass components used in optics and electronics. However, controlling the deformation and fracture mechanisms of glass during embossing remains a significant challenge due to its complex behavior, which can vary between solid and liquid-like states under different conditions. To investigate these mechanisms, this study employs large-scale molecular dynamics (MD) simulations that mirror experimental conditions. The simulations reveal how compressive forces near the mold interface lead to densification and lateral flow of the glass, while tensile stresses at the edges can promote crack formation. Additionally, the study examines the role of strain rate in crack propagation, showing that higher strain rates accelerate failure. These findings offer a deeper understanding of the atomic-level behavior of glass during embossing, highlighting key factors such as stress distribution, energy evolution, and material flow. By bridging the gap between molecular simulations and experimental observations, this work provides valuable insights into optimizing embossing conditions. The results can be applied to improve the quality of glass nanostructures, reducing defects and ensuring the mechanical robustness of glass-based devices.